Juridical Analysis of The Mechanism for Implementing Village Expansion in Holy District - Angga Prastyo Wibowo (Universitas Muhammadiyah Surakarta, 2023)
Implementation of regional autonomy can realize community welfare by improving services and direct community involvement. One of the main attractions of the development of regional autonomy is regional expansion. The scope of regional expansion includes provinces, cities or districts, sub-districts, villages and/or sub-districts. After the reform, Every year regional expansion occurs in many areas throughout Indonesia. One expert, Charles Tibout, has an opinion regarding regional expansion. This expert researched using the public choice school approach contained in his book entitled A Pure Theory of Local Expenditure, which means regional expansion as a model of strong competition in the economic field, where local governments will be able to provide low taxes, effective public services and every individual can free to choose preferences in existing services at every level of government.The government issued Law no. 23 of 2014 in order to increase community welfare, one way is by forming, merging and abolishing regions that cover provinces to villages. This research shows that with the issuance of Law no. 23 of 2014 can improve community welfare.